Activation of Primary Amines by Copper(I)-Based Lewis Acid Promoters in the Solventless Synthesis of Secondary Propargylamines - Cimarelli, Cristina; Navazio, Federica; Rossi, Federico V.; Del Bello, Fabio; Marcantoni, Enrico (Synthesis, 2019)
Primary amines are activated by copper(I)-based Lewis acid promoters in an A3-coupling one-pot solventless reaction with aldehydes and phenylacetylene for the synthesis of secondary propargylamines. The reaction is promoted by a CuSO4/NaI system, a practical precursor of the in situ generated effective CuI/I2 system, that worked well, but only in a restricted number of examples. Substitution of I2 with CeCl3·7H2O in a one-pot two-step reaction provided good yields and a wider applicability, with the added value given by a safer procedure.
Keywords: propargylamines; A3 coupling; primary amines; copper; cerium trichloride; Lewis acids